Journey to Faith: A Creative Exploration of a Personal Journey to the Christian Faith - Haryadi, Timothy (Auckland University of Technology, 2020)
Journey to Faith is a narrative sequence that draws on my experience of becoming a Christian. The story of the sequence follows the creation of a humanoid clay sculpture, which represents my Christian journey from an autoethnographic perspective. This project investigates how to express this deeply personal experience using the mediums of Computer-Generated Imagery (CGI) and Visual Effects (VFX) to creatively visualize the experiences of faith. The story is separated into three acts, with each act exploring an aspect of my journey through surrealist metaphors and references to biblical allegories. This project is informed by theological, as well as philosophical concepts that have contextualized this research and supported the development of the artefact.
Keywords: Christianity; Visual Effects; Autoethnography; phenomenology